Implikasi Penetapan Dispensasi Perkawinan terhadap Kasus Perceraian (Studi Kasus di Pengadilan Agama Sengkang) - Takdir Takdir; Muhammad Farhan Abdullah; Muhammad Tahmid Nur (Neolectura, 2023)
This research discusses the implications of determining marriage dispensation on divorce cases in the Sengkang Religious Court. This type of research is qualitative research with a normative juridical approach. The results of this study show that the relationship between marriage dispensation & divorce is interrelated with each other because it is included in cases in the Religious Court, but the factor that is the background for the application for marriage dispensation is the culture that is always maintained by the people of Wajo Regency to marry off their children even though they are still underage. The background of parents' concern about their children not getting married soon is the fear of their children becoming old virgins. Only about 10% of divorce cases are caused by marital age dispensation, the more factors causing divorce are mostly due to economic problems, continuous quarrels (conflicts), and there was no deep understanding between the couples. The strategic solution to minimize marriage dispensation is to educate children that marrying underage has a high risk, including when giving birth to the child in the future, local governments must also play an active role by issuing rules in the form of laws prohibiting underage marriage. The implications of underage marriage dispensation cause conflicts in the household that lead to divorce, in addition to the cause of death in mothers or babies born due to the absence of physical maturity on the part of women.